KINETICS OF PB RELEASE DURING THE ZIRCON EVAPORATION TECHNIQUE - Chapman H.J.; Roddick J.C. (My University, 1994)
The release of silica and Pb from zircon by the thermal evaporation technique is shown to relate to the conversion of zircon to a porous baddeleyite structure. The zircon-baddeleyite reaction occurs at a sharp reaction front which progressively migrates towards the centre from the grain margin. Significant reaction in non-metamict zircon commences in the mass spectrometer at temperatures of the order of 1500°C. The progressive migration of zircon-baddeleyite transformation towards grain interiors explains why the evaporation technique, with its inherent advantage of not requiring chemical separation of Pb and U, progressively samples Pb in zones towards the centre of the grain and gives 207Pb/206Pb ages as accurate as conventional U-Pb dating methods. The rates of Pb and silica loss are primarily determined by the rate of advance of this de-silicification reaction front towards the interior of the grain. Most estimates of Pb diffusion coefficients in zircon imply that diffusion distances in the unreacted zircon are negligible ( ~ 10-2 mum) at the temperatures and duration of the Pb evaporation experiments. Isothermal experiments demonstrate the rate of zircon-baddeleyite transformation with time and temperature and provide an estimate of 130 +/- 10 (1sigma) kcal . mol-1 for the activation energy of the process, significantly higher than estimates of Pb diffusion activation energy.